2015
DOI: 10.1152/ajpheart.00126.2015
|View full text |Cite
|
Sign up to set email alerts
|

Tetrandrine reverses human cardiac myofibroblast activation and myocardial fibrosis

Abstract: Teng G, Svystonyuk D, Mewhort HE, Turnbull JD, Belke DD, Duff HJ, Fedak PW. Tetrandrine reverses human cardiac myofibroblast activation and myocardial fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…After the injury, various peptide growth factors stimulate fibroblasts to migrate into the wound site and proliferate to reconstitute the various connective tissue components . A critical event in the process is the differentiation of fibroblasts into active‐phenotype myofibroblasts . This differentiation results in functional changes including increased proliferation, changes in the release of signaling molecules, and extracellular matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
“…After the injury, various peptide growth factors stimulate fibroblasts to migrate into the wound site and proliferate to reconstitute the various connective tissue components . A critical event in the process is the differentiation of fibroblasts into active‐phenotype myofibroblasts . This differentiation results in functional changes including increased proliferation, changes in the release of signaling molecules, and extracellular matrix deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Cell morphology and local ECM remodelling by individual myofibroblasts were assessed with the use of a noncontractile collagen gel model as previously described. 11 Morphologic parameters included cell area as determined with the use of the Multi-Cell outliner ImageJ plug-in, number of cell extensions, and length of extensions. Local ECM remodelling was quantified by assessment of collagen fibre alignment with the use of confocal reflectance microscopy and ImageJ software with the Oval Profile plug-in.…”
Section: Assessment Of Cell Morphology and Local Ecm Remodellingmentioning
confidence: 99%
“…Expression of a-SMA was characterized with the use of flow cytometry as previously described. 11 Western blot a-SMA expression and SMAD2/3 phosphorylation was characterized by means of Western blot analysis. the use of confocal microscopy.…”
Section: Alpha-smooth Muscle Actin (A-sma) Expression Characterizationmentioning
confidence: 99%
“…Clinically, TED has been found to be effective for the treatment of inflammation, 1 , 2 pneumosilicosis, 3 and antitumor activity. 4 6 Numerous studies have reported that TED also acts as a nonselective calcium channel blocker 7 , 8 and calmodulin antagonist. 9 In addition, TED has exhibited excellent pharmacological effects, especially in treating pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%